Posterior–Anterior Brain Maturation Reflected in Perceptual, Motor and Cognitive Performance - Gerván, Patrícia; Soltész, Péter; Filep, Orsolya; Berencsi, Andrea; Kovács, Ilona (Frontiers in Psychology, 2017)
Based on several postmortem morphometric and in vivo imaging studies it has been postulated that brain maturation roughly follows a caudal to rostral direction. In this study, we linked this maturational pattern to psychological function employing a series of well-established behavioral tasks. We addressed three distinct functions and brain regions with a perceptual (contour integration, CI), motor (finger tapping, FT), and executive control (Navon global-local) task. Our purpose was to investigate basic visual integration functions relying on primary visual cortex (V1) in CI; motor coordination function related to primary motor cortex (M1) in FT, and the executive control component, switching, related to the dorsolateral prefrontal region of the brain (DLPFC) in the Navon task. 122 volunteer subjects were recruited to participate in this study between the ages of 10 and 20 (females n=63, males n=59). Employing conventional statistical methods, we found that 10 and 12 year olds are performing significantly weaker than 20 year olds in all three tasks. In the CI and Navon global-local tasks, even 14 years old perform poorer than adults. We have also investigated the developmental trajectories by fitting sigmoid curves on our data streams. The analysis of the developmental trajectories of the three tasks showed a posterior to anterior pattern in the emergence of the developmental functions with the earliest development in the visual CI task (V1), followed by motor development in the FT task (M1), and cognitive development as measured in the Navon global-local task (DLPC) being the slowest. Gender difference was also present in FT task showing an earlier maturation for girls in the motor domain.